Cook Islands : Technical Assistance Report-International Financial Services Industry. (IMF Staff Country Reports; Country Report, 2019)
This technical assistance mission report underlines efforts to estimate the economic and revenue contributions of the international financial services industry in the Cook Islands. This report discusses the data and methodology used and presents the results. One matter that has been raised is that international companies are exempt from all taxes in the Cook Islands. The economic contribution of the international financial services industry can be measured by the value added of resident institutional units engaged, directly or indirectly, in the production of international financial services in the Cook Islands. The production of international financial services generates income which is distributed to the various agents or groups of agents who use that income to acquire goods and services for consumption now or later. The international financial services industry also contributes indirectly to gross domestic product through two channels. The first channel is through the goods and services that the industry purchases from other suppliers, such as electricity, accounting services, telecommunications, et cetera.